Preparation, Characterization and Performance of a Novel Surface-Imprinting Polymer for the Adsorption of Dibenzothiophene - Weihong Huang; Wei Zhou; Wanzhen Xu; Pingping Xu; Xiangjun Xu; Yongsheng Yan (Adsorption Science & Technology)
A novel surface-imprinting polymer (MIP/K 2 Ti 6 O 13 ) was prepared using potassium hexatitanate whiskers (K 2 Ti 6 O 13 ) as the carrier employing electrostatic interaction and π–π interaction between the template molecule [dibenzothiophene (DBT)] and the functional monomer [4-vinylpyridine (4VP)]. The synthetic polymer was characterized via Fourier-transform infrared (FT-IR) spectroscopy, surface area and porosity analysis, and X-ray diffraction (XRD). Static adsorption experiments were conducted to evaluate the adsorption kinetics, adsorption isotherms and adsorption selectivity of MIP/K 2 Ti 6 O 13 . Adsorption kinetic studies revealed that a contact time of 300 min was necessary to attain equilibrium. Adsorption isotherm studies indicated that the capacity of MIP/K 2 Ti 6 O 13 towards the adsorption of DBT at 298 K, 308 K and 318 K was 16.18 mg/g, 22.74 mg/g and 29.89 mg/g, respectively. Selectivity experiments showed that the adsorption capacity of DBT on MIP/K 2 Ti 6 O 13 was greater than for the other three analogues, while the imprinting factor towards DBT (α) was 2.06.